(untitled) (Unilorin Journal of Lifelong Education, 2023)
The study examined the relationship between individual characteristics and academic achievement of the undergraduates of University of Lagos. Three research hypotheses were formulated and tested to guide the investigation in the study. The descriptive survey as well as expost-facto research designed was adopted in the study. A sample size of 276 undergraduates in 300 level were randomly selected from four faculties from University of Lagos, through simple random and proportional sampling techniques. A structured self-designed questionnaire titled “Students’ Characteristics and Academic Achievement Questionnaire (SCAAQ) with reliability coefficient of 0.83 was used to collect data for the study. The hypotheses were tested using the Pearson Product Moment Correlation Coefficient at 0.05 level of significance. The findings of the study revealed that there is a significant positive relationship between: (i) achievement motivation and academic achievement of Undergraduates; (ii) study habit and academic achievement; and (iii) students’ self-concept and academic achievement of Undergraduates. Based on the findings, one the recommendations put forth was that the counselling unit of the University should organize conferences and motivational lectures that will impact of undergraduates’ self-concept and academic motivation.